2022
DOI: 10.3389/fmars.2022.968848
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biology of the grenadiers Macrourus caml and M. whitsoni in the Ross Sea region, Antarctica

Abstract: The grenadiers Macrourus caml and M. whitsoni form a significant bycatch component of longline fisheries for Antarctic toothfish (Dissostichus mawsoni) in the Southern Ocean. A lack of species-level biological and catch data has to date hindered the development of quantitative assessments for these deepwater species. This paper examines species- and sex-specific life histories of M. caml and M. whitsoni in the Ross Sea region, Antarctica, from samples collected from the commercial fishery and research collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…Based on historical data and parameters [25], we preliminary estimated that M. whitsoni caught in the Cosmonaut Sea was between 3 and 23 years old and was a long-life cycle fish. Previous studies of M. whitsoni in the Ross Sea revealed that the maximum body length of M. whitsoni ranged from 650 to 680 mm [26][27][28], and the maximum body weight was approximately 1300 g [28], which was similar to the results of our study. Bradley et al calculated parameter b in their study of M. whitsoni in the Ross Sea and found that most of the M. whitsoni samples were distributed at depths of 1200-1400 m [28].…”
Section: Dominant Speciessupporting
confidence: 91%
See 1 more Smart Citation
“…Based on historical data and parameters [25], we preliminary estimated that M. whitsoni caught in the Cosmonaut Sea was between 3 and 23 years old and was a long-life cycle fish. Previous studies of M. whitsoni in the Ross Sea revealed that the maximum body length of M. whitsoni ranged from 650 to 680 mm [26][27][28], and the maximum body weight was approximately 1300 g [28], which was similar to the results of our study. Bradley et al calculated parameter b in their study of M. whitsoni in the Ross Sea and found that most of the M. whitsoni samples were distributed at depths of 1200-1400 m [28].…”
Section: Dominant Speciessupporting
confidence: 91%
“…Previous studies of M. whitsoni in the Ross Sea revealed that the maximum body length of M. whitsoni ranged from 650 to 680 mm [26][27][28], and the maximum body weight was approximately 1300 g [28], which was similar to the results of our study. Bradley et al calculated parameter b in their study of M. whitsoni in the Ross Sea and found that most of the M. whitsoni samples were distributed at depths of 1200-1400 m [28]. Moreover, M. whitsoni is a very abundant species and dominates the fish fauna of deep-sea slopes [26,29,30].…”
Section: Dominant Speciessupporting
confidence: 91%